FILOSOFI TRADISI BEBANTAI DI DESA TANJUNG MUDO, PANGKALAN JAMBU, MERANGIN, JAMBI (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2023)
Customs or traditions passed down by ancestors can fade or even disappear. One of the traditions that is still maintained is the tradition of burdentai by the people of Tanjung Mudo, Jambi. The Bebantai tradition is symbolic, so in that tradition there are symbols that have their own meanings that cannot be directly captured their meanings. Comprehensive research is needed to answer the meaning of the traditional symbol of burdentai. The approach used is descriptive qualitative research, the source as well as the object of research is humans. The data collection method is carried out by observation, interview and documentation techniques. The results of this study can be seen that the tradition of burdentai is the tradition of slaughtering buffalo animals as slaughter animals to welcome the month of Tanjung Mudo. The burdentai tradition is considered by the local community as a form of maintaining good traditions, and upholding cultural values as a reflection of the community itself. The meanings of symbols in the burdentai tradition include: First, kobo (buffalo) which is a hope for society to eliminate the bestiality that exists in humans. Second, the field is a reminder for the community that humans will be gathered in Padang Mahsyar later. Third, auctions become guidelines by the community in competing for good. The four mantai (pray on the day of burdentai) as a conclusion in the tradition of burdentai for the blessings that have been given by Him, both in the form of health and safety so that they can still meet the month of Ramadan. In practice, the tradition of burdentai provides a banquet by gathering in a hall that has been prepared which aims to get smooth running for the hajat intended and led by traditional officials. This burdentai tradition activity includes religious activities aimed at achieving salvation outwardly and inwardly.